2021
DOI: 10.15252/embj.2020107240
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycan processing selects ERAD‐resistant misfolded proteins for ER‐to‐lysosome‐associated degradation

Abstract: Efficient degradation of by‐products of protein biogenesis maintains cellular fitness. Strikingly, the major biosynthetic compartment in eukaryotic cells, the endoplasmic reticulum (ER), lacks degradative machineries. Misfolded proteins in the ER are translocated to the cytosol for proteasomal degradation via ER‐associated degradation (ERAD). Alternatively, they are segregated in ER subdomains that are shed from the biosynthetic compartment and are delivered to endolysosomes under control of ER‐phagy receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 89 publications
(287 reference statements)
2
51
0
1
Order By: Relevance
“…Cytosolic accumulation and aggregation of misfolded proteins upon defective clearance are involved in conditions such as spongiform neurodegeneration and severe ataxia. Misfolded proteins in the ER are translocated to the cytosol for proteasomal degradation via ER-associated degradation (ERAD) [11]. Proteins which do not engage ERAD factors are segregated in ER subdomains and delivered to endolysosomes for ER-to-lysosome-associated degradation (ERLAD) under the control of ER-phagy receptors [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Cytosolic accumulation and aggregation of misfolded proteins upon defective clearance are involved in conditions such as spongiform neurodegeneration and severe ataxia. Misfolded proteins in the ER are translocated to the cytosol for proteasomal degradation via ER-associated degradation (ERAD) [11]. Proteins which do not engage ERAD factors are segregated in ER subdomains and delivered to endolysosomes for ER-to-lysosome-associated degradation (ERLAD) under the control of ER-phagy receptors [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These receptors accumulate, leading to membrane deformation. The subsequent targeting of the ER for degradation often occurs through recruitment of ATG8/LC-3 proteins located on autophagic membranes, followed by engulfment and trafficking of ER membrane to the lysosome (Sun and Brodsky, 2019;Grumati et al, 2018;Fumagalli et al, 2016;Omari et al, 2018;Loi et al, 2019;Fregno et al, 2021). The mechanisms regulating engulfment/scission are unknown.…”
Section: Er-to-lysosomal Associated Degradative (Erlad)mentioning
confidence: 99%
“…Micro-ER-phagy and LC3/Atg8-dependent vesicular delivery described processes where the ER is directly targeted to the lysosome without autophagic engulfment (Fregno and Molinari, 2019). Micro-ER-phagy has been observed during recovery from ER stress, and in response to aggregation of misfolded proteins in the ER that are resistant to ERAD, such as in AATD or procollagen I which will be discussed later in this review (Fregno and Molinari, 2018;Fregno et al, 2021). In mammals, the micro-ER-phagy and LC3-Atg8-dependent vesicular delivery pathways currently identified involve LC-3 lipidation, which targets the ER to interact with endolysosomal membranes followed by fusion of the membranes and degradation of the target proteins (Molinari, 2021).…”
Section: Er-to-lysosomal Associated Degradative (Erlad)mentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, vesicles containing aggregates are fused with endolysosomes to be degraded [ 15 ]. Furthermore, a recent study showed that glucose processing of N-glycans of proteasome-resistant misfolded proteins, such as ATZ, is required for targeting these proteins for degradation by ERLAD [ 24 ]. In this process, CALNEXIN works with UDP-glucose: glycoprotein glucosyltransferase (UGGT1) and other glucose processing enzymes to mediate substrates selection [ 24 ].…”
Section: Er-phagymentioning
confidence: 99%